Relevansi Regulasi Pertambangan Internasional dengan Penanganan Covid-19 di Indonesia - Nasir, Melisa; Hardianti, Inas; kholiyah, Elmi; Fitriani, Fitriani; Tobing, Imanuel CML (Fakultas Syariah INSURI Ponorogo, 2023)
Pressure on the mining industry was caused by global mining activities which experienced disruptions to the demand for and sales of mining materials during the COVID-19 pandemic. The consequences of these events affected world mining production. The purpose of this article is (1) Many small people in the world have not applied the principles of